2019
DOI: 10.1038/s41419-019-2006-2
|View full text |Cite
|
Sign up to set email alerts
|

Response gene to complement 32 expression in macrophages augments paracrine stimulation-mediated colon cancer progression

Abstract: M2-polarized tumor associated macrophages (TAMs) play an important role in tumor progression. It has been reported that response gene to complement 32 (RGC-32) promotes M2 macrophage polarization. However, whether RGC-32 expression in macrophages could play a potential role in tumor progression remain unclear. Here we identified that increasing RGC-32 expression in colon cancer and tumor associated macrophages was positively correlated with cancer progression. In vitro studies confirmed that colon cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In the TME, TAMs and tumor cells promote tumor cell proliferation through the secretion of cytokines. In vitro studies confirmed that colon cancer cells upregulated the expression of RGC-32 in macrophages by secreting TGF-β1, and RGC-32 promoted the migration of macrophages and further accelerated the proliferation of colon cancer cells [61]. Yu, X. et al reported that overexpression of C-X-C-motif receptor 4 (CXCR4) in the intestinal epithelial mucosa can promote epithelial-mesenchymal transition (EMT) and macrophage infiltration in colonic tissue, leading to colitis-associated tumorigenesis and progression [62].…”
Section: Tams Promote Tumor Proliferation Invasion and Migrationmentioning
confidence: 75%
“…In the TME, TAMs and tumor cells promote tumor cell proliferation through the secretion of cytokines. In vitro studies confirmed that colon cancer cells upregulated the expression of RGC-32 in macrophages by secreting TGF-β1, and RGC-32 promoted the migration of macrophages and further accelerated the proliferation of colon cancer cells [61]. Yu, X. et al reported that overexpression of C-X-C-motif receptor 4 (CXCR4) in the intestinal epithelial mucosa can promote epithelial-mesenchymal transition (EMT) and macrophage infiltration in colonic tissue, leading to colitis-associated tumorigenesis and progression [62].…”
Section: Tams Promote Tumor Proliferation Invasion and Migrationmentioning
confidence: 75%
“…Microglia are CNS-resident cells with an instrumental role in driving neuroinflammation ( 71 ). Evidence suggests that RGC-32 regulates macrophage differentiation and functions in various pathologies ( 72 74 ), and since macrophages share the same developmental origin as microglia ( 75 ), we assume that RGC-32 also plays an important role in these cells. In fact, RGC-32 has been shown to be expressed by cells with a microglial morphology in MS brains ( 27 ).…”
Section: Future Directionsmentioning
confidence: 87%
“…TAMs are prevalent in the TME of patients with CRC [ 31 ]. TAMs in the TME are predominantly the M2-type, which are important in cancer cell proliferation and metastasis [ 61 ]. A low M1/M2 ratio indicates poor prognosis and facilitates tumor cell metastasis [ 31 , 62 , 63 ].…”
Section: Modulation Of Tams By Nanomaterials For the Treatment Of Crcmentioning
confidence: 99%